Digital Banking: Assessing Customer Satisfaction through Product Quality - Wiharso, Gani; Akbar Basudani, Wahid; Theresia Simamora, Valentine; Mulyadi, Hary (Dinasti International Journal of Economics, Finance & Accounting, 2022)
The fastest growth of information technology and the digital disruption which massively increase brought a huge impact to the banking field to continue their efforts to innovate the products. This research aims to explore whether the quality of the products offered by Bank Syariah Indonesia can improve the quality of its customers. The method that currently applied on this research was quantitative by causal approach. The sample which has been studied were 75 Indonesian Islamic Bank customers who were selected by random sampling technique. The technique chooses to selected the data was through a questionnaire. And These research reveals that an innovative product quality can be a factor that will improve the customer satisfaction area. With this research, Bank Syariah Indonesia is expected to implement and innovate their ultimate digital banking products which kindly difficult to imitate, and have high use value and cannot be replaced by other products, so as to achieve customer satisfaction and sustainable competitive advantage.